2011
DOI: 10.1105/tpc.111.083121
|View full text |Cite
|
Sign up to set email alerts
|

A Member of the PLEIOTROPIC DRUG RESISTANCE Family of ATP Binding Cassette Transporters Is Required for the Formation of a Functional Cuticle in Arabidopsis

Abstract: Although the multilayered structure of the plant cuticle was discovered many years ago, the molecular basis of its formation and the functional relevance of the layers are not understood. Here, we present the permeable cuticle1 (pec1) mutant of Arabidopsis thaliana, which displays features associated with a highly permeable cuticle in several organs. In pec1 flowers, typical cutin monomers, such as v-hydroxylated fatty acids and 10,16-dihydroxypalmitate, are reduced to 40% of wild-type levels and are accompani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
170
0
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(175 citation statements)
references
References 63 publications
3
170
0
2
Order By: Relevance
“…9, M-P). The polar localization has been also reported in other ABCG proteins, such as AtABCG11 (Panikashvili et al, 2007) and AtABCG32 (Bessire et al, 2011). The protein localization signal is also in agreement with previous reported expression patterns of OsABCG15 (Qin et al, 2013;Zhu et al, 2013).…”
Section: Osabcg15 Is Mainly Localized On the Plasma Membrane Of Tapetsupporting
confidence: 79%
See 1 more Smart Citation
“…9, M-P). The polar localization has been also reported in other ABCG proteins, such as AtABCG11 (Panikashvili et al, 2007) and AtABCG32 (Bessire et al, 2011). The protein localization signal is also in agreement with previous reported expression patterns of OsABCG15 (Qin et al, 2013;Zhu et al, 2013).…”
Section: Osabcg15 Is Mainly Localized On the Plasma Membrane Of Tapetsupporting
confidence: 79%
“…Some plant ABCG proteins have been reported to contribute to the synthesis of extracellular barriers. In Arabidopsis, ABCG11 (Cuticular Defect and Organ Fusion1/DESPERADO/White-Brown Complex11; Bird et al, 2007;Panikashvili et al, 2007Panikashvili et al, , 2010, ABCG12 (Eceriferum5/WBC12; Pighin et al, 2004), ABCG13 (Panikashvili et al, 2010), ABCG29 (Alejandro et al, 2012), ABCG32 (Bessire et al, 2011), and ABCG26 (WBC27; Xu et al, 2010;Quilichini et al, 2010Quilichini et al, , 2014Choi et al, 2011;Dou et al, 2011) have been shown to be involved in transport of lipidic compounds. Notably, it has been reported that these ABCG proteins have a broad substrates spectrum (for example, ABCG11 transports both cutin and wax monomers, and ABCG13 and ABCG32 mainly transport cutin monomers, whereas ABCG12 mainly transports wax precursors, and ABCG29 mainly transports monolignol).…”
mentioning
confidence: 99%
“…A series of Arabidopsis mutants defective in cuticle synthesis and secretion show the biological roles of cuticles as a barrier to biotic or abiotic stresses, osmotic stress, water loss, and damage from UV radiation, and in preventing the fusion of leaves and floral organs (Yephremov et al, 1999;Pruitt et al, 2000;Krolikowski et al, 2003;Aharoni et al, 2004;Kurdyukov et al, 2006;Bessire et al, 2007;Shi et al, 2011;Wang et al, 2011). Some mutants are known to be involved in petal morphogenesis: Lack of nanoridges of petals, due to a mutation in DEFECTIVE IN CUTICULAR RIDGES (DCR, encoding a BAHD acyltransferase), CYP77A6 (cytochrome P450 family), GLYCEROL-3-PHOSPHATE ACYLTRANSFERASE6 (GPAT6), or PERMEABLE CUTICLE1 (PEC1), result in increased permeability of petals to a dye and cause organ fusion (Li-Beisson et al, 2009;Panikashvili et al, 2009;Bessire et al, 2011). Compared with these Left and right halves show the petal structure in the wild type and fop1, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is possible that Lr34sus-D, Lr34-B, OsABCG50 and the two sorghum orthologs have conserved functions. For example, two recent studies identified three orthologous ABCG transporters from barley, rice and Arabidopsis that are all involved in the formation of cutin layers (Bessire et al 2011;Chen et al 2011).…”
Section: Lr34 Haplotypes In Wheat Rice and Sorghummentioning
confidence: 99%